ASCE honor for the Tczew bridge in Poland - Cywiński, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This note presents the background for the introduction of the quoted bridge, as the International Civil Engineering Landmark, on the list of the ASCE History and Heritage Program. The history and the key structural features of that bridge have been briefly discussed. The opinion has been expressed that this long-span lattice-tube girder bridge could be regarded, really, as an ingenious child of the famous tubular Britannia Bridge in England. The observation of a matching, open-minded and global historic landmark policy of the ASCE has been positively underlined.
Keywords: mosty; Tczew; ASCE; bridges